Strukturální analýza romské religiozity na příkladu rituální praktiky "přísahy u kříže" - Jakoubek, Marek; Budilová, Lenka J. (2014)
Abstract: The following text is based on the outcomes of a long-term field research carried out in eastern Slovakia, and it focuses on the character and specifics of religiosity of the Romany settlements inhabitants. One of the characteristic features of this religiosity is the fact that its core is still based on magical practices while Christianity only covers it on the surface. We will attempt to document this feature by examining a particular example of a chosen institution, this institution being the ritual procedure of the oath at the cross. Even though this practice is commonly known and frequently mentioned in literature, we are of the opinion that most references have so far been of the character of a mere record without an attempt to comprehend its inner nature. Thus, our objective is to explore the intrinsic logic of this institution, which may moreover be helpful in terms of illuminating the whole of the religious system of the Romany settlements inhabitants because in many aspec